Ultra-Low-Dose CT of the Thorax Using Iterative Reconstruction: Evaluation of Image Quality and Radiation Dose Reduction - Kim, Yookyung; Kim, Yoon Kyung; Lee, Bo Eun; Lee, Seok Jeong; Ryu, Yon Ju; Lee, Jin Hwa; Chang, Jung Hyun (American journal of roentgenology (1976), 2015)
The purpose of this study is to assess the image quality and radiation dose reduction of ultra-low-dose CT using sinogram-affirmed iterative reconstruction (SAFIRE). This prospective study enrolled 25 patients who underwent three consecutive unenhanced CT scans including low-dose CT (120 kVp and 30 mAs) and two ultra-low-dose CT protocols (protocol A, 100 kVp and 20 mAs; protocol B, 80 kVp and 30 mAs) with image reconstruction using SAFIRE. The image quality and radiation dose reduction were assessed. The mean (± SD) effective radiation dose was 1.06 ± 0.11, 0.44 ± 0.05, and 0.31 ± 0.03 mSv for low-dose CT, ultra-low-dose CT protocol A, and ultra-low-dose CT protocol B, respectively. Overall image quality was determined as diagnostic in 100% of low-dose CT scans, 96% of ultra-low-dose CT protocol A scans, and 88% of ultra-low-dose CT protocol B scans. All patients with nondiagnostic quality images had a body mass index (weight in kilograms divided by the square of height in meters) greater than 25. There was no statistically significant difference in detection frequencies of 14 lesion types among the three CT protocols, but pulmonary emphysema was detected in fewer patients (3/25) in ultra-low-dose CT protocol B scans compared with ultra-low-dose CT protocol A scans (5/25) or low-dose CT scans (6/25). We measured the longest dimensions of 33 small solid nodules (3.8-12.4 mm in long diameter) and found no statistically significant difference in the values afforded by the three CT protocols (p = 0.135). Iterative reconstruction allows ultra-low-dose CT and affords acceptable image quality, allowing size measurements of solid pulmonary nodules to be made.